2021
DOI: 10.3390/socsci10020040
|View full text |Cite
|
Sign up to set email alerts
|

Household Social Expenditure in Ghana: Examining the Ex-Post Effects and Vulnerability to Poverty

Abstract: We estimate the effect of household social expenditure on vulnerability to poverty using the four latest cross-sectional waves of Ghana Living Standard Survey (GLSS) from 1999 to 2017. Using a 3-Stage Least Square and Quantile Regression, our results show a widening consumption ex-post welfare gap between the poorest households and the non-poor households in a per-dollar social expenditure. Further, we estimate the probability of an ex-ante poverty using vulnerability to expected poverty. The results, however,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Yet based on these results this is not the case (Deressa 2013 ). Nkrumah et al ( 2021 ) found the same results and argue that because those in urban areas rent as opposed to own their properties unlike people living on farms. Thus, this allows farm owners to generate income from their land, and hence, they can reduce vulnerability to poverty at a greater margin than urban dwellers.…”
Section: Resultsmentioning
confidence: 68%
“…Yet based on these results this is not the case (Deressa 2013 ). Nkrumah et al ( 2021 ) found the same results and argue that because those in urban areas rent as opposed to own their properties unlike people living on farms. Thus, this allows farm owners to generate income from their land, and hence, they can reduce vulnerability to poverty at a greater margin than urban dwellers.…”
Section: Resultsmentioning
confidence: 68%
“…Poor families may appear to have improved their welfare through social spending, but in reality, this practice is not good for poor families in future poverty analysis. As a result, the idea of social investment through social spending may not be entirely true for the poor, especially without clear compensatory trade-offs for increasing family income (Nkrumah et al, 2021;Visagie & Turok, 2021). The issue of inequality and poverty has always been a fundamental problem in the study of development in rural areas (Anastasiou et al, 2021;Peterson, 2017;Xu & Takahashi, 2021).…”
Section: Introductionmentioning
confidence: 99%